Perancangan Furnitur Musikal untuk Ruang Tunggu Publik - Paulinesya, Yeshua Monica; Mulyono, Grace; Tanaya, Frenky (Intra, 2019)
Musical Furniture is furniture whose function is combined with musical instruments. The furniture that will be designed consists of furniture wich is generally placed in the public waiting room, including low stool, bench, side table, coffee table. The purpose of this musical furniture is to express the sound produced by furniture-making materials and also to preserve the local culture of East Java by appliying some of its distinctive instruments into the furniture. It is not enough to convey what musical furniture is on paper, so the author makes a full scale. The targeted user of this furniture are 15-45 years old adult, so this musical furniture is designed in a simple form to be easily played.                The design method used is the experimental method and research adapted from the Chabsrock company regarding objects, namely about furniture materials and musical instrument to combine with furniture